(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The problem of emotional weariness among doctors is examined in this study, along with its signs and root causes. The essay was based on research that uncovered emotional tiredness syndrome in students and doctors across many specialties. Burnout, its manifestations, and its etiologies within the realm of medical practitioners. The paper originated from a research that investigated the recognition of emotional tiredness syndrome among students and doctors across various specialties.